Perceptions of oral and maxillofacial surgery amongst Australian medical general practitioners. Issue 3 (May 2018) - Lababidi, Emad; Breik, Omar; Subramaniam, Shiva
Abstract: Objective: This study was undertaken to identify the proportion of referrals to Oral and Maxillofacial surgeons amongst Australian general medical practitioners (GP's) for common head and neck surgical scenarios. Methods: A questionnaire presenting 34 common clinical surgical scenarios involving the head and neck region, as well as a descriptive component identifying reasons/barriers to referral was sent out through newsletter e-publications targeting general practitioners. The main outcome measures were identification of the preferred specialty referral (Ear Nose and Throat, Plastic, Oral & Maxillofacial (OMS) or General surgery) for each of the clinical scenarios provided. Results: 90 GP's participated with eligible responses. The majority of dento-alveolar surgery and facial trauma was referred to OMS. In cases of oral pathology, the referral rate to OMS was mixed (mean ∼57%). Regarding facial cosmetics, the majority of respondents chose Plastic Surgery for referrals (94.4%), and ENT surgery for the management of obstructive sleep apnoea (90%). Conclusions: The responses of this survey indicate an adequate awareness of the core fields in OMS (trauma, dento-alveolar). Less awareness appears to be present of the expanding role of OMS in the areas of pathology and cosmetic and OSA surgery. Medical education may play a role in expanding these perceptions.